Those Near At Hand: Family In The Novels Of Saul Bellow. - Paglia, Mark. (Tufts Archival Research Center, 2005)
A survey of family roles as they appear in the novels The Adventures of Augie March, Seize the Day, Henderson the Rain King, Herzog, and Humboldt's Gift. This branches into discussion of the protagonists' and the author's views on American identity, gender roles, and ambivalence over adult responsibility.